(untitled) (Research, Society and Development, 2023)
Urinary tract infections are common during pregnancy and can lead to negative outcomes, such as pre-eclampsia, prematurity and low birth weight. Therefore, health professionals must diagnose them and propose appropriate antimicrobial treatment. The objective of this article is to review recent information on urinary tract infections during pregnancy, emphasizing the best antimicrobial therapy for each case. To this end, articles from the last five years were reviewed on the SciELO and PubMed platforms, available in English or Portuguese. Within the 27 studies found, those that addressed topics other than those covered in this research were excluded. As a result, 10 articles were selected. In addition, guiding reference documents on the topic were included, such as national and international protocols and guidelines. From them it was realized that, during pregnancy, it is essential to screen for asymptomatic bacteriuria through urine culture. The diagnosis of cystitis and pyelonephritis is clinical, through anamnesis and physical examination. In these cases, urine culture must be performed to identify the causative agent, which is especially important if resistant bacteria are found. There is different information regarding treatment in the articles researched. However, most texts considered nitrofurantoin, cephalosporins, phosphomycin and amoxicillin as adequate and safe options for the treatment of asymptomatic bacteriuria or cystitis, with duration of therapy depending on the chosen antimicrobial. For cases of pyelonephritis, the importance of hospitalizing the pregnant woman was explained, with cephalosporins selected as initial therapy. In short, there is conflicting information regarding the choice of antimicrobials and the recommended treatment duration for urinary tract infections during pregnancy. Therefore, more research is required to disseminate more accurate information, improve treatment and avoid bacterial selection.